2022
DOI: 10.3389/fmicb.2022.924137
|View full text |Cite
|
Sign up to set email alerts
|

Differences in microbial diversity and environmental factors in ploughing-treated tobacco soil

Abstract: During agricultural production, plowing affects the existing traits of the planted soil, including environmental factors (physicochemical properties and soil enzymatic activity) and microbial community, but whether deep tillage and conventional tillage cause differences in soil microecology are unknown. In this study, the 16S rRNA high-throughput sequencing technology was combined with soil environmental factor detection to analyze the differences in microbial diversity of smokey soils at different depths. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Elusimicrobia was unique to the rare group of bacteria. Zhao et al ( 2021 ) and Zhang et al ( 2022 ), reported that Firmicutes and Entotheonellaeota show a high correlation with soil nutrient content, while rare groups of Elusimicrobia in bacterial communities had no correlation with soil nutrient content. It seems clear that the input of organic fertilizer has increased the portion of class Clostridia, which belongs to Firmicutes and may degrade the lignin and cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…Elusimicrobia was unique to the rare group of bacteria. Zhao et al ( 2021 ) and Zhang et al ( 2022 ), reported that Firmicutes and Entotheonellaeota show a high correlation with soil nutrient content, while rare groups of Elusimicrobia in bacterial communities had no correlation with soil nutrient content. It seems clear that the input of organic fertilizer has increased the portion of class Clostridia, which belongs to Firmicutes and may degrade the lignin and cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of nine antibiotics [norfloxacin (NOR), ofloxacin (OFL) and ciprofloxacin (CIP), oxytetracycline (OTC), tetracycline (TC), sulfapyridine (SPD) and sulfadiazine (SDZ), erythromycin (ERM) and roxithromycin (ROM)] was extracted and determinated according to our previous study ( Zhang et al, 2022 ; Supplementary Table S1 ). Briefly, the antibiotics in the extract were determined by liquid chromatography-mass spectrometry (LC-ESI-MS/MS) in multiple reactive ion detection mode (MRM).…”
Section: Methodsmentioning
confidence: 99%
“…Soil microorganisms are an important part of the ecosystem and play an important role in maintaining soil ecological functions [7,8]. Microbial community structure can reflect the quality and health of soil to a certain extent, which is of great value in exploring the functional characteristics of soil and the structural properties of the ecosystem [9]. Previous studies have shown that AR can lead to soil acidification [10][11][12], which can promote an increase in the concentration of hydrogen ions in soil and cause changes in the composition and structure of soil microbial communities [13].…”
Section: Introductionmentioning
confidence: 99%